Інтродукція Liquidambar styraciflua L. в Україні та успішність його акліматизації в Національному ботанічному саду імені М.М. Гришка НАН України - Smilyanets, Nina; Svitylko, Іgor (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2025)
Liquidambar styraciflua L. plants were screened in all soil and climatic zones of Ukraine in artificial phytocenoses of urban areas, i.e., botanical gardens, parks, squares, green areas, residential areas, and streets.Considering L. styraciflua plants growing in the M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv) as an example, their introduction success by the acclimatization degree, including the indicators of growth, generative development, winter hardiness, and drought resistance, was calculated. The acclimatization degree of the tested plants reached 90 points, corresponding to a good acclimatization level.Hence, L. styraciflua can be recommended for use in landscape construction to create groups, alleys, or as tapeworms in parks, squares, zoos, landscaping streets, boulevards, squares, adjacent areas near houses and administrative buildings, and private estates. These plants can also be successfully applied in expositions of botanical gardens and arboretums and as objects of topiary art.